Introduction - Bordonaro, L.; Carvalho, C. (Cadernos de Estudos Africanos, 2010)
The purpose of this special issue is to explore and question the link between generation and change and look at the ambiguous and troubled relationship between youth and social and cultural change in contemporary Africa. The challenge we take up is that of assessing the role of youth in social transformation processes, geting rid of the pitfalls of notions of modernity or modernisation as theoretical tools, but without overlooking the remarkable cultural dynamics that characterise contemporary Africa. While it is indeed untenable to understand contemporary Africa in terms of modernity, we cannot overlook that the African present has much to do with the impact of and reaction to expansive markets, mass media and commoditisation, and with colonial and postcolonial Euro- American expansion. Nor can we ignore the powerful hold that the idea of modernity has in many popular fields of discourse, in local contexts, state policies and international institutions.